2020
DOI: 10.1101/2020.05.29.122986
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk factors associated with mortality in hospitalized patients with SARS-CoV-2 infection. A prospective, longitudinal, unicenter study in Reus, Spain

Abstract: 20Spain is one of the countries that has suffered the most from the impact of severe acute 21 respiratory syndrome coronavirus 2 (SARS-CoV-2), the strain that causes coronavirus disease 22 2019 (COVID-19). However, there is a lack of information on the characteristics of this disease in 23 the Spanish population. The objective of this study has been to characterize our patients from 24 an epidemiological point of view and to identify the risk factors associated with mortality in our 25 geographical area. We pe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
12
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
7
12
2
Order By: Relevance
“…Interestingly, we observed more features associated with mortality in our cohort, but age seems to be the most important risk factor for COVID‐19, which is in line with other published studies 26,44‐47 . The predictive role of age is also confirmed by Sun et al, De Smet et al, 47 and Chen et al 45 studies.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, we observed more features associated with mortality in our cohort, but age seems to be the most important risk factor for COVID‐19, which is in line with other published studies 26,44‐47 . The predictive role of age is also confirmed by Sun et al, De Smet et al, 47 and Chen et al 45 studies.…”
Section: Discussionsupporting
confidence: 92%
“…We have previously reported the main epidemiological and clinical characteristics and the mortality risk factors of the first wave patients during a month and a half between March and April [11]. In the present investigation we extended the study to mid-October to cover two equal periods of three and a half months.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, cancer had the highest odds ratio among all other risk factors. Respiratory problems, especially chronic lung disease worsen the patients' condition and increase mortality [ 36 , 38 ]. A recent study showed that longer history of COPD results in more negative outcomes and more death rate [ 38 ].…”
Section: Discussionmentioning
confidence: 99%